Promising prospective effects of Withania somnifera on broiler performance and carcass characteristics: A comprehensive review - Salem, Heba M.; El-Saadony, Mohamed T.; Abd El-Mageed, Taia A.; Soliman, Soliman M.; Khafaga, Asmaa F.; Saad, Ahmed M.; Swelum, Ayman A.; Korma, Sameh A.; Gonçalves Lima, Clara Mariana; Selim, Samy; Babalghith, Ahmad O.; Abd El-Hack, Mohamed E.; et al. (Frontiers in Veterinary Science, 2022)
Poultry production contributes markedly to bridging the global food gap. Many nations have limited the use of antibiotics as growth promotors due to increasing bacterial antibiotic tolerance/resistance, as well as the presence of antibiotic residues in edible tissues of the birds. Consequently, the world is turning to use natural alternatives to improve birds’ productivity and immunity. Withania somnifera, known commonly as ashwagandha or winter cherry is abundant in many countries of the world, is considered a potent medicinal herb because of its distinct chemical, medicinal, biological, and physiological properties. This plant exhibits antioxidant, cardioprotective, immunomodulatory, anti-ageing, neuroprotective, antidiabetic, antimicrobial, antistress, antitumor, hepatoprotective, and growth-promoting activities. In poultry, dietary inclusion of W. somnifera revealed promising results in improving feed intake, body weight gain, feed efficiency, and feed conversion ratio, as well as reducing mortality, increasing livability, increasing disease resistance, reducing stress impacts, and maintaining health of the birds. This review sheds light on the distribution, chemical structure, and biological effects of W. somnifera and its impacts on poultry productivity, livability, carcass characteristics, meat quality, blood parameters, immune response, and economic efficiency.